Smart Grow Light: Sistema de Internet das Coisas para manejo de alfaces e microverdes em cultivo indoor com iluminação artificial. - Vieira, Lucas Bryan Lima (2024)
In an era driven by the technology of the fourth industrial revolution, producing on a large scale and maintaining quality is what everyone expects. The need for food production on the planet is increasing, with United Nations projections that, from 2050 onwards, the world population will exceed 10 billion people. In view of this factor, humanity needs to develop new agricultural techniques to provide, efficiently and on a large scale, healthier food to humanity. However, the availability of processed, transgender and industrialized foods poses a challenge for those who seek to take care of their health without losing the practicality of the modern world. Keeping these factors in mind, farmers, engineers and scientists have sought to implement new cultivation techniques by implementing modern technologies adorned with sustainable development. Faced with these challenges, the present work aimed to develop a system composed of hardware and software for the intelligent indoor cultivation of vegetable gardens with artificial lighting using the internet of things. The research methodology involved three stages: 1) Systematic Literature Review to investigate equipment and techniques used in the cultivation of indoor vegetable gardens; 2) Development of an architecture composed of hardware and software for intelligent indoor cultivation of vegetable gardens with artificial lighting; 3) Validation of the proposed architecture based on an experiment consisting of the installation of hardware and software devices to monitor the stages of indoor vegetable cultivation. For the experimentation stage, lettuce and beet microgreens, red cabbage and mustard were planted in a cabin that monitors the environmental variables of temperature and humidity inside and outside the cabin and automatically monitors the air fans, air and LED panel remotely via Wi-Fi, Zigbee and Bluetooth on the Tuya Smart app. The results obtained point to a system composed of hardware and software with full vegetable production capacity through its complete development from sowing, germination, transplanting and harvesting, producing beetroot and red cabbage microgreens without the emergence of fungi or any other insect problems during the observation period.